Recycling of Food Waste to Produce the Plant Fertilizer - R. Ahmed, Rand; I. Abdulla, Aziz (International Journal of Engineering and Technology, 2018)
Around 5000 tons of food waste is produced every day in Iraq which accounts for about (50%) of the waste that we get rid of them. Waste sent to landfill for disposal may break down and produce methane gas that causes greenhouse effect, as well as cause odor, epidemics, and disease because of the disintegration. The research aims to produce organic fertilizer through the recycling of domestic refuse. It has been working through this research to collect the domestic refuse food which represent the nitrogen source, as well as the remains of cleaning and trimming of various trees and the remains of lawn mowers, and use of sawdust white wood which represent the carbon source. Have been working on dried and arranged in layers of perforated plastic containers for ventilation, it was moisturized with two different types of water and monitored fertilizer maturity for four months. Previously the fresh water was used for the purpose for moisturizing the mixture (chlorination water supply) later the domestic wastewater have been used. The comparison was made between the results of tests performed; the test has come up with the result that the use of "domestic wastewater" which it is rich in living organismsÂ  is the best and fastest in the process of manufacturing organic fertilizer than the use of "water supply", to contain the latter on the amount of chlorine of weakens the growth of microorganisms. And the use of dried plant waste, in the mixture as source of carbon was successful, and it gave the best organic fertilizer production results because these wastes are easy to decompose compare with sawdust wood. The felicitous fertilizer is it rich with nutrient such as nitrogen 2.3 %, phosphorus 13%, and potassium 20%, etc. There are some important factors affecting the process of production of fertilizer, including air ventilation, temperature, moisture content in the mixture. Carbon to nitrogen is a major factor, where each 20-30 part of the carbon should be taken into account for the decomposition of 1 part of the nitrogen to produce the compost properly, the high proportion of carbon about 30%, causes low-temperature mixture, and it leads to slow compost composition, and less than 20% leads to excess nitrogen, which lost in the air in the form of ammonia, and the higher pH value, could be toxic to some microorganisms.Â Â